PENERAPAN PENDEKATAN SAVI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI GAYA MEMPENGARUHI GERAK DAN BENTUK BENDA - Putri, Galuh Mutiara; Panjaitan, Regina Lichteria; Sujana, Atep (Jurnal Pena Ilmiah, 2017)
This research is motived by the problem of low student learning outcomes on the material influences the motion and shape of objects in class IV SDN Cipameungpeuk Sumedang Subdistrict South Sumedang District. Improvement efforts to overcome these problems by appliying the SAVI approach with Classroom Action Research methods that implemented 3 cycles and each cycle consists of planning, implementation, observation, and reflection. Each aspect has a significant improvement in each cycle, with teacher performance percentage at 57% initial data, 84% cycle I, 91% cycle II, and 100% cycle III. For percentage of activity ininitial data obtained 0%, cycle I 17%, cycle II 54%, and 92% cycle III.Â  Thus it can be concluded that the implementation of SAVI approach can improve student learning outcomes on the material style affect the motion and shape of objects